2021
DOI: 10.1039/d0ra09820e
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and irreversible membrane fouling in hollow-fiber UF membranes filtering surface water: effects of ozone/powdered activated carbon treatment

Abstract: This study investigated the reversible and irreversible membrane fouling behavior of micro polluted water by ozone/powdered activated carbon (PAC)/ultrafiltration treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The principle of this method to explore the SOC effect of perovskite has been fully discussed in previous publications. [43][44][45] Simply put, circularly polarized photoexcitation generates excitons with electrons of same-oriented orbital magnetic dipoles, providing strong magnetic dipole momenta through orbit-orbit interaction to create a photoinduced SOC. This photoinduced SOC can convert photogenerated excitons of a bright state into a dark state which is more difficult to recombine due to the spin selection rule.…”
Section: Resultsmentioning
confidence: 99%
“…The principle of this method to explore the SOC effect of perovskite has been fully discussed in previous publications. [43][44][45] Simply put, circularly polarized photoexcitation generates excitons with electrons of same-oriented orbital magnetic dipoles, providing strong magnetic dipole momenta through orbit-orbit interaction to create a photoinduced SOC. This photoinduced SOC can convert photogenerated excitons of a bright state into a dark state which is more difficult to recombine due to the spin selection rule.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane fouling resistances were compared over the three phases to assess the differences in fouling control between the VCMBR and the ASCMBR. , Table shows that intrinsic membrane resistance ( R m ) in both MBRs were consistent at 2.60 ± 0.05 (×10 11 m –1 ) because an identical ceramic membrane module was used in each bioreactor. It is clear that the main fouling resistance in both MBRs was reversible fouling ( R r ), contributing to over 72.9% of the total membrane fouling resistance ( R t ) in all three phases as consistently reported in earlier studies. , …”
Section: Resultsmentioning
confidence: 99%
“…Experimental characterizations, such as SEM (scanning electron microscopy), AFM, and water contact angle analysis, were carried out to compare the results with other pristine PVDF membranes, and it was observed that CND-blended membranes had larger surface pores, thus demonstrating higher water permeability and lesser roughness on the surface. Moreover, the irreversible fouling ratio to the total fouling ratio ( R ir / R t ) dropped from 85% for the pure PVDF membrane to 21% for the CND-blended membrane. , …”
Section: Physical and Chemical Characteristics Of Bioartificial Membr...mentioning
confidence: 97%
“…Moreover, the irreversible fouling ratio to the total fouling ratio (R ir /R t ) dropped from 85% for the pure PVDF membrane to 21% for the CNDblended membrane. 44,45 Many of these synthetic polymers are either avoided for use in biomedical applications or modified through biological/ chemical means to tailor their surfaces to be suitable for bioengineering applications. At the same time, natural polymers, although being promising for developing membranes for bioengineering, suffer from poor mechanical and manufacturing processability.…”
Section: Physical and Chemical Characteristics Of Bioartificial Membr...mentioning
confidence: 99%
See 1 more Smart Citation